EVALUATION OF DENTIST’S SATISFACTION OF MARGINAL FIT IN FIXED PARTIAL DENTURES FABRICATED USING CAD/CAM SYSTEMS - AN INSTITUTION BASED RETROSPECTIVE STUDY - Sri, Harini; Ahmed, Nabeel; Shashanka, Keerthi (International Journal of Psychosocial Rehabilitation, 2019)
Accuracy and quality of CAD CAM in producing fixed partial dentures, crowns and bridges is acceptable and improving every day. Marginal adaptation is one of the most important factors for success and clinical longevity of the treatment. The aim of this study was to retrospectively evaluate the dentist’s satisfaction of marginal fit in fixed partial dentures fabricated using CAD/CAM systems. The data for this study was collected from June 2019 to March 2020 at a private dental institution in Chennai. A total of 507 patients who received fixed partial dentures were included in the study. Data regarding the marginal fit in relation to each sextant was collected from the case record. Chi-square test was applied to see associations of marginal fit satisfaction in each sextant. The results showed that 94.1% (n=477) of the fixed partial dentures a satisfactory marginal fit, while the marginal fit in 5.9% (n=30) of the FPDs were non satisfactory. Fixed partial dentures in sextant 2 showed 30% (n=9) non satisfaction followed by sextant 1 with 20% (n=6). The findings of this study shows that the FPDs fabricated using CAD/CAM systems had a satisfactory marginal fit and comparatively sextant 2 presented with high marginal misfit than the other sextants.